Experiment and Analysis Briquette Cob Upon Which Burn Producer of Vapour - Eswanto; Barita Siregar; Ricad P. Girsang (Jurnal Teknik Mesin, 2017)
In Indonesia Corn is one of the second type of food crop, this condition based on physical characteristics and corn chemical has potential as a source of biomass energy. Corncob biomass waste can be made into corncob briquettes to produce environmentally friendly alternative energy, where the utilization of biomass as energy is done by combustion in the combustion chamber, which in this case is stoker. The purpose of this research is to know the characteristics and efficiency of burning corncobs and corncob briquettes as steam-producing biomass fuels. The experimental method was experiment with combustion of corncob briquettes with 10%, 20%, 30% adhesive variation on stocker combustion chamber using air supply 0,00144 m3 / s, air excess 10% (0,00158 m3 / s), and excess Air 20% (0,00173 m3/s) with valve angle 15º, 17º, 18º, and feeding fuel 0,1 kg, 0,15 k, 0,2 kg, fuel is put into continuous combustion chamber using conveyor. The calorific value of 10% tuna corncob briquettes HHV= 8578,38 kJ/kg, LHV= 5338.38 kJ/kg, 20% adhesive HHV= 6127,41 kJ/kg, LHV= 2887,43 kJ/kg, adhesive 30% HHV= 6127,41 kJ/kg, LHV: 2887,43 kJ/kg using a calorimeter boom analysis. Temperature generated on burning 10cm tuna corncob briquettes reach 906 ºC and at the lowest temperature of 284 ºC, 20% adhesive reaches 901 ºC and at the lowest temperature of 225 ºC, 30% adhesives reach 829 oC and at the lowest temperature of 250 ºC. Efficiency of combustion chamber of briquettes 10% cobber cornet briquettes are η: 69%, adhesive 20% η = 66%, adhesive 30% η = 67%. From the results of this type of corn tuna briquette fuel with adhesive variation, fuel on 10% adhesive produces the highest temperature and efficiency.